Gallium Sulfide-Immobilized Optical Fiber-Based SPR Sensor for Detection of Brilliant Blue Food Adulteration - Nasih Hma Salah; Baljinder Kaur; Hogr M. Rasul; Yesudasu Vasimalla; Chella Santhosh; Ramachandran Balaji; S. R. Srither; Santosh Kumar (IEEE Open Journal of Nanotechnology)
Food safety assurance is crucial, particularly in identifying prohibited colors like brilliant blue (BB) that may pose significant health risks when used in food products. Surface plasmon resonance (SPR) biosensors provide a reliable, label-free method for highly sensitive detection of food adulterants. In this study, we present a novel gallium sulfide (GaS)-immobilized optical fiber SPR sensor designed for the rapid, real-time detection of BB synthetic dye. The proposed sensor is comprised of a high birefringence layer (HBL) core with non-added formaldehyde (NaF) cladding, silver (Ag) as the plasmonic metal, and GaS for enhanced detection sensitivity. To determine the sensor performance, the wavelength-dependent response was measured at different refractive indices (RIs), together with sensitivity and figure of merit (FOM) over the wavelength range of 400 nm to 1000 nm. The parameters were evaluated in a sensing medium consisting of water and BB under concentrations ranging from 10 mM to 600 mM. Moreover, the distribution of electromagnetic fields across the multilayer structures of the sensor, particularly at the interfaces between Ag-GaS and GaS-analytes, was investigated. At a 10 mM concentration, the optimized Ag-GaS-based sensor, consisting of 70 nm Ag and 3 nm GaS layers at an incidence angle of 85°, achieves a maximum sensitivity of 5119.6 nm/RIU and FOM of 255.98 RIU-1. The obtained results illustrate the sensor has the potential to detect non-approved colors like BB in food items with great sensitivity and accuracy.